PERANAN KETERANGAN AHLI KEDOKTERAN JIWA DALAM PROSES PENYIDIKAN DI KEPOLISIAN RESOR KOTA PEKANBARU - Devi Indriani; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The book of the law of criminal procedure mentioned in Article 184 of the evidence. Witness testimony is one of valid evidence. Investigation is a series of actions the investigator to find evidence so as to make light of a criminal offsense. The purpose of this study is first, to determine the role of expert psychiartric testimony in the investigation process. Secondly, to determine the strength of a psychiatric expert testimony as one type of evidence in the investigation process. Kind of this research is empirical jurisdiction, namely by approaching problems examined with real law in accordance with the reality on the ground. In this study the authors directly conduct research on the location or point studied to provide complete the problem. This research conducted in Pekanbaru City Police and Tampan Mental Hospital. Population and sample are those relating to the issue, examined in this study, the source of the data used is a primary data, secondary data and data tertiary. Data collection techniques in this study is observation, interview and literature study. From the research, there are two main problems can be inferred. First, a psychiatric expert investigators need coordinate for some case requiring medical expert testimony. Secondly, despite expert testimony is valid evidence, the need for further guidance on the use of expert testimony. Advice writer first, expected to be made a spesific rule governing the unity of a letter of expert psychiatric testimony. Secondly, investigator should not believe the psychological status of suspects only by a certificate of mental illness. Investigators should be highlighting a history of psychiatric suspect.Keywords: Role – Expert Psychiatric- Investigations